In vivo and in vitro evaluation of a biodegradable magnesium vascular stent designed by shape optimization strategy. (November 2019) - Chen, Chenxin; Chen, Jiahui; Wu, Wei; Shi, Yongjuan; Jin, Liang; Petrini, Lorenza; Shen, Li; Yuan, Guangyin; Ding, Wenjiang; Ge, Junbo; Edelman, Elazer R.; Migliavacca, Francesco
Abstract: The performance of biodegradable magnesium alloy stents (BMgS) requires special attention to non-uniform residual stress distribution and stress concentration, which can accelerate localized degradation after implantation. We now report on a novel concept in stent shape optimization using a finite element method (FEM) toolkit. A Mg-Nd-Zn-Zr alloy with uniform degradation behavior served as the basis of our BMgS. Comprehensive in vitro evaluations drove stent optimization, based on observed crimping and balloon inflation performance, measurement of radial strength, and stress condition validation via microarea-XRD. Moreover, a Rapamycin-eluting polymer coating was sprayed on the prototypical BMgS to improve the corrosion resistance and release anti-hyperplasia drugs. In vivo evaluation of the optimized coated BMgS was conducted in the iliac artery of New Zealand white rabbit with quantitative coronary angiography (QCA), optical coherence tomography (OCT) and micro-CT observation at 1, 3, 5-month follow-ups. Neither thrombus or early restenosis was observed, and the coated BMgS supported the vessel effectively prior to degradation and allowed for arterial healing thereafter. The proposed shape optimization framework based on FEM provides an novel concept in stent design and in-depth understanding of how deformation history affects the biomechanical performance of BMgS. Computational analysis tools can indeed promote the development of biodegradable magnesium stents. Graphical abstract: Image 1